Reliability Based Life Cycle Management of Bridge Subjected to Fatigue Damage - Stipanovic, Irina; Connolly, Lorcan; Skaric Palic, Sandra; Duranovic, Marko; Donnelly, Róisín; Bernardini, Ilaria; Bakker, Jaap (Frontiers in Built Environment, 2020)
The number of transport infrastructure failures is increasing due to the ageing, increased number of extreme weather events caused by climate change, and increased traffic loading. Accordingly, the need for planned and unplanned maintenance interventions is rising. Associated costs do not only involve direct maintenance or reconstruction costs, but also secondary effects experienced by users of the transport network as well as the environment and the society in general. Infrastructure managers are in need of tools for accurate quantification of infrastructure resilience that will enable rational adaptation investment strategies, so as to maintain high level of safety of transport networks. Through the development of a Global Safety Framework, at the core of which is a Multi-modal Network Decision Support Tool, the SAFE-10-T project (Safety of Transport Infrastructure on the TEN-T Network) is providing integrated solutions to issues related to infrastructure safety and planning. The paper presents a reliability-based whole life cycle model developed within this project enabling strategic investment decisions that maximize safety, minimize disruption and environmental impacts and allow for the best use of limited resources. The model is applied on a case study of a bridge in the Port of Rotterdam in the Netherlands.